Dust evolution with MUPPI in cosmological volumes. Issue 2 (19th July 2022) - Parente, Massimiliano; Ragone-Figueroa, Cinthia; Granato, Gian Luigi; Borgani, Stefano; Murante, Giuseppe; Valentini, Milena; Bressan, Alessandro; Lapi, Andrea
ABSTRACT: We study the evolution of dust in a cosmological volume using a hydrodynamical simulation in which the dust production is coupled with the MUPPI (MUlti Phase Particle Integrator) sub-resolution model of star formation and feedback. As for the latter, we keep as reference the model setup calibrated previously to match the general properties of Milky Way-like galaxies in zoom-in simulations. However, we suggest that an increase of the star formation efficiency with the local dust-to-gas ratio would better reproduce the observed evolution of the cosmic star formation density. Moreover, the paucity of quenched galaxies at low redshift demands a stronger role of active galactic nucleus feedback. We tune the parameters ruling direct dust production from evolved stars and accretion in the interstellar medium to get scaling relations involving dust, stellar mass and metallicity in good agreement with observations. In low-mass galaxies, the accretion process is inefficient. As a consequence, they remain poorer in silicate and small grains than higher mass ones. We reproduce reasonably well the few available data on the radial distribution of dust outside the galactic region, supporting the assumption that the dust and gas dynamics are well coupled at galactic scales.